Regulatory T cells and organ transplantation. - Waldmann, H; Graca, L; Cobbold, S; Adams, E; Tone, M; Tone, Y (2004)
Empirical studies attempting to explain tolerance to transplanted tissues have demonstrated a regulatory role for CD4+ T-cells. We here propose that regulatory T-cells mediating transplantion tolerance comprise two sets which can functionally complement each other. The CD4+CD25+ "natural regulator" arises in the thymus, and is preoccupied with self-antigens expressed at sites of inflammation. The second, comprising both CD4+CD25+ (FoxP3+) and CD4+CD25- Tr1-like cells are induced by persistent danger-free antigen in the periphery. The role of these cells is to moderate immune responses to prevent tissue destruction while allowing microbial elimination.